1990
DOI: 10.1002/eji.1830200306
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of T lymphocyte heparanase by heparin prevents T cell migration and T cell‐mediated immunity

Abstract: Previously we reported that activated T lymphocytes express a heparanase enzyme that degrades the heparan sulfate moiety of the proteoglycan of the extracellular matrix (ECM). Expression of the heparanase enzyme was found to be associated with the ability of activated T lymphocytes to penetrate blood vessel walls and accumulate in target organs. We recently found that relatively low doses of heparin administered to mice or rats inhibited T cell-mediated immune reactions. In the present study we investigated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
123
0
1

Year Published

1991
1991
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 149 publications
(124 citation statements)
references
References 21 publications
0
123
0
1
Order By: Relevance
“…The shaved abdominal skin of inbred BALB/c mice (The Jackson Laboratory, Bar Harbor, ME; groups of 10 females) was sensitized with 100 l of 2% (v/v) oxazalone dissolved in acetone/olive oil (4:1 (v/v)), applied topically (16). DTH sensitivity was elicited 5 days later by challenging the mice with 10 l of 0.5% oxazalone in acetone/olive oil, applied topically to each side of the ear.…”
Section: Dth Assaymentioning
confidence: 99%
“…The shaved abdominal skin of inbred BALB/c mice (The Jackson Laboratory, Bar Harbor, ME; groups of 10 females) was sensitized with 100 l of 2% (v/v) oxazalone dissolved in acetone/olive oil (4:1 (v/v)), applied topically (16). DTH sensitivity was elicited 5 days later by challenging the mice with 10 l of 0.5% oxazalone in acetone/olive oil, applied topically to each side of the ear.…”
Section: Dth Assaymentioning
confidence: 99%
“…The effects of low-molecular-weight, heparin-like molecules on the rejection process were first described by Lider et al 15 in a mouse skin-allograft model. They reported that low doses of heparin-like molecules without anticoagulant effects altered T-lymphocyte functions in vitro 22 and in vivo. 15 Reports indicate that T lymphocytes have an endoglycosidase that specifically degrades the heparan sulfate side chains of the extracellular proteoglycans in vitro.…”
Section: Heparin Effectsmentioning
confidence: 99%
“…The closely related molecule heparan sulphate is, however, found on vascular endothelial cells, where it is considered to play a role in preventing non-speci®c adhesion of blood elements since it is now known that certain in¯ammatory cells, most notably lymphocytes, release heparan-degrading enzymes in order to aid their extravasation (reviewed by Vlodavsky et al, 1992) and that these enzymes are inhibited by heparin (Bar-Ner et al, 1987). Indeed, the inhibitory e ects of administered heparin on lymphocyte orchestrated processes such as graft vs host reactions (Gorski et al, 1991;Lider et al, 1989), delayed type hypersensitivity reactions (Sy et al, 1983) and allergic encephalomyelitis (Lider et al, 1990;Willenborg & Parish, 1988) are thought to involve heparanase inhibition. However, there is also evidence that heparin can a ect the entry of lymphocytes to lymph nodes and Peyer's patches (Bellavia et al, 1980), having potential consequences with respect to the recirculation of these cells.…”
Section: Introductionmentioning
confidence: 99%